Ionic strength induced electrodeposition of two-dimensional layered MoS2 nanosheets - Rastogi, Pankaj Kumar; Sarkar, Sujoy; Mandler, Daniel (APPLIED MATERIALS TODAY, 2017)
A new redox-free electrochemical approach for driving the deposition of two-dimensional (2D) layered MoS2 nanosheets is described. First, poly(acylic acid) (PAA) functionalized layered MoS2 nanosheets (PAA-MoS2) is prepared to form a stable aqueous PAA-MoS2 dispersion, which is subsequently used for the electrochemical deposition. In contrast to previous electrodeposition methods of MoS2, which involve the redox of molecular precursors of Mo and S, herein we introduce an electrochemical approach for the deposition of 2D layered MoS2 nanosheets directly from their nanometric building blocks, namely from their aqueous dispersion. This ‘‘nano to nano’’ approach is based on altering the ionic strength at the vicinity of the electrode surface by applying a potential. Specifically, the electrogeneration of Cue-1 ions, cause the PAA-MoS2 nanosheets in the dispersion to aggregate and deposit on the copper electrode. Scanning electron microscopy, X-ray diffraction, Raman and X-ray photoelectron spectroscopy analysis show clearly that the deposited layered MoS2 maintains its original structure. Furthermore, the ;electrodeposited PAA-MoS2 nanosheets on copper show excellent catalytic activity for the hydrogen evolution reaction with low overpotential. Hence, we believe that these findings could lead to a generic approach for the formation of thin films or patterns of 2D nanomaterials. (C) 2017 Elsevier Ltd. All rights reserved.